Psychological symptoms of COVID-19 epidemic: A systematic review of current evidence - Seyed Alinaghi Seyed Ahmad; Karimi Amirali; Shobeiri Parnian; Nowroozi Ali; Mehraeen Esmaeil; Afsahi Amir Masoud; Barzegary Alireza (Psihologija, 2021)
Since the outbreak of COVID–19, several published reports of increased psychological problems turned the attention towards this field and ignited controversies surrounding it. Our aim was to address the issues in this area of interest to provide information for a more robust approach. We carried out a systematic search in PubMed, Embase, Scopus, UpToDate, Science direct, and Web of Science databases. We included English-written original papers, abstracts, reports, and letters to the editor published from December 2019 to April 2020. After evaluating the title and abstract to select the most relevant papers based on inclusion and exclusion criteria, articles underwent quality assessment. The full text of selected articles was then thoroughly read to extract the essential findings. The current review of the literature showed that psychological symptoms might happen among most people, including medical staff, and patients during the COVID–19 epidemic. We identified 24 potential psychological symptoms of the SARS-CoV–2 public health emergency. Reviewing extracted studies revealed that there was a risk of occurrence of psychological symptoms among the general population during the COVID–19 outbreak. However, firstline medical staffs who provide healthcare services to patients with COVID–19 were more susceptible to these symptoms. The systematic review highlights that anxiety, depression, stress, and sleep disturbance symptoms were the most frequent psychological symptoms of the COVID–19 pandemic situation. It is recommended that future studies evaluate practical interventions to reduce psychological symptoms, especially in health care workers during the COVID–19 epidemic.